2012
DOI: 10.1371/journal.pone.0032417
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for Absorption of Water-Soluble Secondary Metabolites Greater in Birds than in Rodents

Abstract: Plant secondary metabolites (SMs) are pervasive in animal foods and potentially influence feeding behavior, interspecies interactions, and the distribution and abundance of animals. Some of the major classes of naturally occurring SMs in plants include many water-soluble compounds in the molecular size range that could cross the intestinal epithelium via the paracellular space by diffusion or solvent drag. There are differences among species in paracellular permeability. Using Middle Eastern rodent and avian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 64 publications
9
27
0
Order By: Relevance
“…Previous work showed that this time period is long enough to measure fractional absorption of arabinose (Fasulo et al, 2013a ]-L-arabinose recoveries by 1.11 to account for this difference in probe recovery, producing an 'adjusted cumulative % injection dose recovered'. Although L-arabinose is not metabolized and theoretically can be fully recovered, recoveries of injected inert probes are often less than 100% (Karasov et al, 2012). To account for this loss, we normalized our gavage data using the i.p.…”
Section: Assessment Of L-arabinose Fractional Absorptionmentioning
confidence: 99%
“…Previous work showed that this time period is long enough to measure fractional absorption of arabinose (Fasulo et al, 2013a ]-L-arabinose recoveries by 1.11 to account for this difference in probe recovery, producing an 'adjusted cumulative % injection dose recovered'. Although L-arabinose is not metabolized and theoretically can be fully recovered, recoveries of injected inert probes are often less than 100% (Karasov et al, 2012). To account for this loss, we normalized our gavage data using the i.p.…”
Section: Assessment Of L-arabinose Fractional Absorptionmentioning
confidence: 99%
“…The degree of use of the paracellular pathway varies widely among vertebrates (Caviedes-Vidal et al, 2007; Fasulo et al, 2013a). For example, it is minor in terrestrial mammals, but several small birds and bats actually absorb the majority of glucose paracellularly (Karasov and Cork, 1994;Caviedes-Vidal and Karasov, 1996;Levey and Cipollini, 1996;Afik et al, 1997;Tracy et al, 2007;Karasov et al, 2012;Fasulo et al, 2013b). This phenomenon has been hypothesized to derive from an evolutionary pressure to reduce mass in flying animals (CaviedesVidal et al, 2007) while having as a trade-off greater exposure to water-soluble toxins (Diamond, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the passive pathway is less selective than a carrier-mediated system, birds may be more vulnerable to hydrophilic secondary metabolites (Diamond 1991). Karasov et al (2012), using two bird species (including yellow-vented bulbuls) and two rodent species,…”
Section: Secondary Metabolites and The Paracellular Pathwaymentioning
confidence: 99%
“…Sugars such as sucrose, glucose and fructose are the main nutrients in nectar and fruits (Baker et al 1998;Martínez del Rio et al 1992) and their efficient digestion depends in part on passive absorption by the paracellular pathway, especially in small birds and bats (CaviedesVidal et al 2007;Karasov et al 2012;Napier et al 2008). This could be disadvantageous for consumers if fruits and nectar contain hydrophilic secondary metabolites, because they will be easily absorbed by the paracellular route (Diamond 1991;Karasov et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation